STUDI PENGGUNAAN HANDOUT DALAM MODEL PEMBELAJARAAN KOOPERATIF TIPE ARTIKULASI TERHADAP PEMBELAJARAN MATEMATIKA SISWA KELAS X JURUSAN ADMINISTRASI PERKANTORAN (AP) SMKN 1 KOTA SOLOK - Adhia, Hana (JURNAL LEMMA, 2017)
The result of student learning is low because the several factors, they are. Difficult for the student to understand the material,  So that  the student lazy to read and student to chat with their friend while learning. The solutions to overcome the problem is using the articulation desaign of learning and used handout to study. The purpose of this study was to determine the result of mathematics learning at the firs grade of office administration at SMKN 1 Kota Solok used handout in cooperative learning type articulation better than without used handout. This research is quasi eksperimental desaign. Population in this research is at the first grade of office administration at SMKN 1 Kota Solok 2015/2016 academic year. Sampel this research is class X office administration 1 as eksperimental class total 36 students and class X office administration 5 as control class total 36 students. Data collection in this research using test the result of mathematics learning such as essai consist 5 question. Data analisis the result of student learning got    dan  = 1,64 So   table so hypothesis be accepted to  Can be concluded that the result of mathematics learning at the firs grade of office administration at SMKN 1 Kota Solok used handout in cooperative learning type articulation better than without used handout.